Subclinical VZV reactivation in immunocompetent children hospitalized in the ICU associated with prolonged fever duration2. (18th January 2013) - Papaevangelou, V.; Quinlivan, M.; Lockwood, J.; Papaloukas, O.; Sideri, G.; Critselis, E.; Papassotiriou, I.; Papadatos, J.; Breuer, J.
Abstract: A prospective observational study was conducted to examine whether asymptomatic VZV reactivation occurs in immunocompetent children hospitalized in an ICU and its impact on clinical outcome. A secondary aim was to test the hypothesis that vaccinated children have a lower risk of reactivation than naturally infected children. Forty immunocompetent paediatric ICU patients and healthy controls were enrolled. Patients were prospectively followed for 28 days. Clinical data were collected and varicella exposure was recorded. Admission serum levels of TNF‐a, cortisol and VZV‐IgG were measured. Blood and saliva samples were collected for VZV‐DNA detection via real‐time PCR. As a comparison, the detection of HSV‐DNA was also examined. Healthy children matched for age and varicella exposure type (infection or vaccination) were also included. VZV reactivation was observed in 17% (7/39) of children. Children with VZV reactivation had extended duration of fever (OR = 1.17; 95% CI, 1.02–1.34). None of the varicella‐vaccinated children or healthy controls had detectable VZV‐DNA in any blood or saliva samples examined. HSV‐DNA was detected in saliva from 33% of ICU children and 2.6% of healthy controls. Among children with viral reactivation, typing revealed wild‐type VZV and HSV‐1. In conclusion, VZV reactivation occurs in immunocompetent children under severe stress and is associated with prolonged duration of fever.